ÓLEOS VEGETAIS NA ALIMENTAÇÃO DE PEIXES: REVISÃO BIBLIOGRÁFICA (REMUNOM, 2025)
The use of vegetable oils in fish nutrition has proven to be a viable strategy for replacing animal-based lipid sources, reducing costs, and ensuring an adequate supply of essential fatty acids. This study reviews the literature on the effects of including vegetable oils in fish diets, with an emphasis on growth, feed efficiency, fillet composition, and the impact on the quality of the final product. The silver catfish (Rhamdia quelen) has been a relevant experimental model for evaluating the effects of different vegetable oils, such as soybean, canola, and rice oil, in aquaculture.